2002
DOI: 10.1016/s0045-6535(02)00061-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical contaminants in juvenile gray whales (Eschrichtius robustus) from a subsistence harvest in Arctic feeding grounds

Abstract: Gray whales are coastal migratory baleen whales that are benthic feeders. Most of their feeding takes place in the northern Pacific Ocean with opportunistic feeding taking place during their migrations and residence on the breeding grounds. The concentrations of organochlorines and trace elements were determined in tissues and stomach contents of juvenile gray whales that were taken on their Arctic feeding grounds in the western Bering Sea during a Russian subsistence harvest. These concentrations were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…The levels found were comparable to those measured in liver and kidney of dead calves from PV [25]. Lower or similar levels of Al to those measured in our study were also found in liver, kidney and brain of juvenile gray whales (Eschrichtius robustus) from a subsistence harvest [35]. However, they were higher than those reported in livers of bowhead whales [36].…”
Section: Discussionsupporting
confidence: 88%
“…The levels found were comparable to those measured in liver and kidney of dead calves from PV [25]. Lower or similar levels of Al to those measured in our study were also found in liver, kidney and brain of juvenile gray whales (Eschrichtius robustus) from a subsistence harvest [35]. However, they were higher than those reported in livers of bowhead whales [36].…”
Section: Discussionsupporting
confidence: 88%
“…Most interestingly, they found no signifi cant differences in the concentrations from whales collected in the more pristine Kodiak Island/Washington outer coastal areas versus those collected in the more impacted areas of Puget Sound, Washington, and San Francisco. Tilbury et al ( 2002 ) sampled gray whales from a subsistence harvest in the Arctic during the fall of 1994 and compared their DDT concentrations (per lipid weight) with those of stranded gray whales from the same general collection area. They discovered signifi cant differences in the harvested versus stranded whale blubber concentrations of males (200 ± 38 ppb versus 39,000 ± 23,000 ppb), females (360 ± 66 ppb versus 2,800 ± 1,000 ppb) and juveniles (330 ± 53 ppb versus 11,000 ± 4,300 ppb), respectively.…”
Section: Ddt In Marine Mammalsmentioning
confidence: 99%
“…Such studies, however, are obviously not classified as minimally to non-invasive (e.g. Tilbury et al 2002;Brown et al 2014). Nevertheless, in addition to capture-and-release studies, studies using harmless sampling methods in live marine mammals are definitely gaining momentum.…”
Section: Overview Of In Vivo In Vitro and In Silico Research Directimentioning
confidence: 99%